Handbook of applicable mathematics Vol I - Ledermann, Edited by: Walter; Ledermann, Walter; Vajda, Steven ([S.l.] : Wiley, 1980)
The main thrust is to provide up-to-date and easily accessible information about the practical aspects of all mathematics and is specifically addressed to users of mathematics who are not professional mathematicians. The work is comprehensive in that all mathematical topics, which are actually being used or are considered valuable for further developments, are covered. The editors and publishers have gone to great lengths to ensure that no branch of mathematics is omitted which is useful and, conversely, that none is included which is not.